CHANGES IN DIFFERENTIAL GENE EXPRESSION PATTERN IN FLY HEADS AS THE RESPONSE TO AN EXPERIMENTALLY EVOLVED X CHROMOSOME - Manat, Y.; Issabekova , A.S.; Kaukabayeva , G.K. (Eurasian Journal of Applied Biotechnology, 2022)
Sexually antagonistic (SA) mutations that increase fitness in one sex and decrease it in the other sex (also known as intralocus sexual conflict) are central to the sexual antagonism hypothesis of sex chromosome evolution. It was suggested long ago (by Fisher, in 1931) that tight linkage to a sex-determining locus facilitates the accumulation of SA mutations even when their detrimental effect in one sex exceeds its benefit in the other. Due to the difficulties in detecting SA alleles directly, we know very little about the nature of X-linked SA mutations and their role in the evolution of differential gene expression between sexes. To investigate how X-linked SA mutations affect the transcriptome profile in both sexes, we analyzed changes in genome-wide gene expression pattern in Drosophila melanogaster head tissue that had undergone 95 generations of a female-limited X-chromosome experimental evolution. We found an evidence of change in gene expression towards to the female optimum, which we interpret as the result of resolution of sexual conflict over X-linked SA mutations. In addition, we also found a potential unknown gene expression effect of the balancer chromosome on gene expression (that was necessary to use to limit the inheritance of target X chromosome to the female line). All these findings indicate that a highly polymorphic nature of the X chromosome with an important role in genome-wide gene expression profile.